National Hospital Ambulatory Medical Care Survey, 2001 ([Verlag nicht ermittelbar], 2003)
The NHAMCS provides data from samples of patient records selected from emergency departments (EDs) and outpatient departments (OPDs) of a national sample of hospitals. The resulting national estimates describe the use of hospital ambulatory medical care services in the United States. For the 2001 survey, data were collected from 224 OPDs and 364 EDs. Among the variables included are age, race, and sex of the patient, reason for the visit, physician's diagnoses, cause of injury (ED only), surgical procedures (OPD only), medication therapy, and expected source of payment.